2023
DOI: 10.1039/d2cc06803f
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric response in polydiacetylene at the single domain level using hyperspectral microscopy

Abstract: The colorimetric response of polydiacetylene was observed at the single microdomain level via hyperspectral microscopy, revealing the blue-to-red transition patterns unique to each stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…PDA derivatives are formed by the self-assembly of diacetylene (DA) monomers, such as 10,12pentacosadiynoic acid (PCDA), followed by subsequent UV irradiation for the polymerization. Upon exposure to different stimuli such as mechanical stress, [2,3] pH, [4] temperature, [5][6][7] DOI: 10.1002/admi.202300745 a blue-to-red colorimetric transition occurs, [8] where only the red polymer is fluorescent. A large number of experimental studies, including the surface pressure measurement by the Langmuir-Blodgett technique, [9] X-ray crystallography, [10] fluorescence spectroscopy, [8] Raman/infrared (IR) spectroscopy, [11,12] nuclear magnetic resonance (NMR), [13] scanning tunneling microscopy (STM), [14] atomic force microscopy (AFM), [15] combined with theoretical studies [16] have provided a mechanistic model, where the torsion of the sidechains shortens the 𝜋−𝜋 conjugation in the backbone, resulting in broadening the bandgap to cause the blue shift in the absorption.…”
Section: Introductionmentioning
confidence: 99%
“…PDA derivatives are formed by the self-assembly of diacetylene (DA) monomers, such as 10,12pentacosadiynoic acid (PCDA), followed by subsequent UV irradiation for the polymerization. Upon exposure to different stimuli such as mechanical stress, [2,3] pH, [4] temperature, [5][6][7] DOI: 10.1002/admi.202300745 a blue-to-red colorimetric transition occurs, [8] where only the red polymer is fluorescent. A large number of experimental studies, including the surface pressure measurement by the Langmuir-Blodgett technique, [9] X-ray crystallography, [10] fluorescence spectroscopy, [8] Raman/infrared (IR) spectroscopy, [11,12] nuclear magnetic resonance (NMR), [13] scanning tunneling microscopy (STM), [14] atomic force microscopy (AFM), [15] combined with theoretical studies [16] have provided a mechanistic model, where the torsion of the sidechains shortens the 𝜋−𝜋 conjugation in the backbone, resulting in broadening the bandgap to cause the blue shift in the absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Since our setup was originally developed for mechanochromic materials, here it would be beneficial to provide its brief introduction for the understanding of the following methodological sections. Polydiacetylene (PDA) is a mechanochromic polymer that changes its color from blue to red and emits fluorescence upon exposure to chemical and physical stimuli. It has garnered particular attention in sensing fields such as the detection of ions, mechanical force, temperature, volatile organic compunds, and biomolecules. ,,, Its mechanochromic principle originates from the twist of the backbone that shortens the conjugation length. The mechanochromic properties of PDA at nanoscale have been investigated by standard AFM by several groups. ,,, These works have shown that PDA responds primarily to the force lateral to the substrate, whereas the application of vertical force did not trigger its fluorescence efficiently.…”
Section: Polydiacetylenementioning
confidence: 99%
“…Polydiacetylene (PDA) is a linear conjugated polymer with triple and double bonds alternating in its backbone. It exhibits unique optical properties, such as a strong red shift in the absorption spectrum and activation of fluorescence upon various stimuli, presenting photochromism, mechanochromism, , ionochromism, thermochromism, affinochromism or biochromism, and solvatochromism . PDAs are known to exist in two primary chromatic phases: an initial metastable blue phase that arises directly after the topochemical photopolymerization of diacetylene monomers and a stable red phase that develops with prolonged UV irradiation or by other stimuli.…”
Section: Introductionmentioning
confidence: 99%